»Kako postanemo stari?« - Remec, Meta (Prispevki za novejšo zgodovino, 2024)
The article discusses the changes in the perception of old age and ageing since the end of the 18th century when this phenomenon transformed from a natural and self-evident process leading to imminent death and transition to eternity to a problem for which a solution had to be found through medicalisation and pathologisation. The methods for prolonging life and tackling the issues involved in ageing have remained almost unchanged since Hippocrates and Galen, except that at the beginning of the 20th century, in addition to a healthy lifestyle and the avoidance of vices, it also became possible to influence the course of aging with the help of various (pseudo-)scientific methods that aroused a great deal of optimism and hope. The article describes the most popular medical and surgical methods promising life extension and eternal youth, the dubious preparations of healers that spread thanks to advertising, and points out the specific nature of the information available to Slovenian readers.
Keywords: ageing; ageing women; dolgoživost; Dr Serge Voronoff; dr. Serge Voronoff; longevity; macrobiotics; makrobiotika; staranje; staranje žensk